Capacities and Needs Assessment on Health Emergency Management in Biliran Province, Philipines - Willard N. Riveral; John Anthony D. Ramagos; Marian Madelyn M. Collera; Jeremy B. Ohiman (Jurnal Ners, 2021)
Introduction: This study aimed to describe the level of preparedness of the healthcare facilities and the healthcare professionals concerning the four components (Health, Psychosocial and Mental Health, Nutrition on Emergencies, and Water Sanitation and Hygiene) of the Health Emergency Management System (HEMS) in the province of Biliran.Methods: The researchers used a sequential explanatory research design and utilized two sets of research instruments for the purpose of data gathering. The participants were healthcare workers from Rural Health Units (RHUs) and representatives from the Local Government Units (LGUs) in Biliran province in the Philippines. For the analysis of the quantitative data, a qualified statistician analyzed the raw data transcribed using the SPSS IMB 21 tool. The qualitative data was analyzed and processed using Mayring and Miles-Huberman’s technique.Results: The study found that the respondents were suitable to provide reliable data and to credibly assess the condition of the RHUs. They were also knowledgeable enough to determine the gaps confronting the RHUs, including their corresponding solutions. The healthcare facilities of the province were only rated to be average. Their capacity to provide post-traumatic counselling was poor, although their referral systems were rated excellent.Conclusion: The study concludes that the healthcare workers of Biliran Province and the HEMS of the eight RHUs in the province are not prepared to manage health emergencies during disasters. The low capacity of the HEMS is due to the low utilization of the budget, resulting in insufficient supplies and equipment which is necessary when addressing people’s immediate needs during disasters and health emergencies. The study recommends a thorough deliberation of the system to plug the gaps and provide rapid equitable health services during emergencies.